Solid electrolyte membrane, preparation method and lithium battery

By combining hyperbranched polymer electrolytes with inorganic electrolytes and lithium salts, a composite solid electrolyte membrane with high mechanical strength and high ionic conductivity was prepared, which solved the problem of insufficient mechanical strength and conductivity in the existing technology and improved the overall performance of lithium batteries.

CN121293495APending Publication Date: 2026-01-09ZHEJIANG LEAPENERGY TECH CO LTD +1

Patent Information

Application Number
CN202511613037.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2026-01-09

AI Technical Summary

Technical Problem

Existing solid electrolyte membranes cannot simultaneously meet the requirements of mechanical strength and conductivity, especially polyethylene oxide materials which have low mechanical strength and insufficient room temperature ionic conductivity.

Method used

By combining hyperbranched polymer electrolytes with inorganic electrolytes and lithium salts, a branched structure is formed through the amidation reaction of triacid anhydride compounds and polyethylene oxide diamine. Combined with ball milling dispersion of inorganic electrolytes, a composite solid electrolyte membrane with high mechanical strength and high ionic conductivity is prepared.

Benefits of technology

It improves the mechanical strength and ionic conductivity of the solid electrolyte membrane, reduces interfacial impedance, and enhances the safety and electrical performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121293495A_ABST
    Figure CN121293495A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte membrane, a preparation method and a lithium battery. The solid electrolyte membrane comprises a polymer electrolyte, the structure of the polymer electrolyte is a hyperbranched polymer, a molecular chain of the polymer electrolyte contains a polyoxyethylene chain segment, ether oxygen atoms in an amorphous phase region can form coordination with lithium ions, migration of the lithium ions is facilitated, and the ionic conductivity of the solid electrolyte membrane is improved; besides, a nitrogen and sulfur element annular structure is introduced into the hyperbranched polymer, so that the mechanical strength of the solid electrolyte membrane can be effectively improved, the ionic conductivity of the solid electrolyte membrane can be further improved, the interface impedance can be reduced, and the comprehensive performance of the battery on safety performance and electrical performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of solid-state lithium batteries, and particularly relates to a solid-state electrolyte film, a preparation method thereof and a lithium battery. BACKGROUND

[0002] At present, lithium ion batteries are widely applied due to their high specific energy, high working voltage, long cycle life, low self-discharge rate and environmental friendliness. However, the traditional liquid lithium ion battery contains an organic carbonate liquid electrolyte, which has poor thermal stability and is flammable. When the battery is misused and generates heat, there are potential safety hazards such as liquid leakage, fire and explosion. Compared with the traditional liquid lithium ion battery, the solid-state lithium battery has higher energy density and higher safety, and has become a research hotspot in the field of lithium batteries.

[0003] The polymer solid-state electrolyte is light in mass, easy to film, has good processability and interface wettability, and is an ideal material for preparing the electrolyte of the solid-state lithium battery. However, the mechanical strength of the polymer solid-state electrolyte is low. Taking polyethylene oxide commonly used in solid-state electrolytes as an example, not only the mechanical strength is low, but also the room temperature ionic conductivity is low, which seriously affects the electrical performance of the battery.

[0004] Therefore, how to develop a composite solid-state electrolyte with high mechanical strength and excellent electrochemical performance is currently urgent to be solved. SUMMARY

[0005] The application aims to provide a solid-state electrolyte film, a preparation method thereof and a lithium battery, and aims to solve the problem that the existing solid-state electrolyte film cannot simultaneously meet the requirements of mechanical strength and conductivity.

[0006] The first embodiment of the application provides a solid-state electrolyte film, which comprises a polymer electrolyte, and the structural formula of the polymer electrolyte is shown as formula I:

[0007] Formula I; In the formula, n=1~100.

[0008] In some embodiments, an inorganic electrolyte and a lithium salt are further included. The mass ratio of the polymer electrolyte, the inorganic electrolyte and the lithium salt is (60~90):(5~20):(5~20).

[0009] In some embodiments, the inorganic electrolyte is a solid-state particle, and the particle size of the solid-state particle is 100~500nm.

[0010] In some embodiments, the inorganic electrolyte comprises Li 3.3 La 0.56 TiO3, Li7La3Zr2O12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 Li3P3S 11 Li2P2S6 and Li 10 GeP2S 12 at least one of the above.

[0011] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis-trifluoromethylsulfonylimide, lithium bisfluorosulfonylimide, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluoro oxalate borate, and lithium perchlorate.

[0012] The second embodiment of the present application provides a preparation method of a solid-state electrolyte film, for preparing the solid-state electrolyte film in any of the above embodiments, comprising the following steps: mixing a trianhydride compound and polyoxyethylene diamine, performing first stirring, adding acetic anhydride and pyridine, performing second stirring, to obtain a polymer electrolyte; adding an inorganic electrolyte to a first organic solvent, performing sufficient ball milling dispersion, to obtain an inorganic electrolyte dispersion liquid; adding the polymer electrolyte to a second organic solvent, heating and performing third stirring, reducing to room temperature, adding the inorganic electrolyte dispersion liquid and a lithium salt, performing fourth stirring, and drying, to obtain the solid-state electrolyte film; wherein, the trianhydride compound has a structural formula as shown in formula II:

[0013] formula II.

[0014] In some embodiments, the mass ratio of the trianhydride compound and polyoxyethylene diamine is 1:4-10.

[0015] In some embodiments, the mass ratio of the polymer electrolyte, the inorganic electrolyte, and the lithium salt is (60-90):(5-20):(5-20).

[0016] In some embodiments, the temperature of the first stirring is 15-30°C, and the time is 20-30h.

[0017] In some embodiments, the temperature of the second stirring is 15-30°C, and the time is 10-20h.

[0018] In some embodiments, the temperature of the third stirring is 45-85°C, and the time is 2-5h.

[0019] In some embodiments, the temperature of the fourth stirring is room temperature, and the time is 1-3 hours.

[0020] In some embodiments, the inorganic electrolyte comprises Li 3.3 La 0.56 TiO3, Li7La3Zr2O 12 , Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 , Li3P3S 11 , Li2P2S6 and Li 10 GeP2S 12 .

[0021] In some embodiments, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis-trifluoromethylsulfonylimide, lithium bisfluorosulfonylimide, lithium tetrafluoroborate, lithium bisoxalate borate, lithium difluoro oxalate borate, and lithium perchlorate.

[0022] In some embodiments, the first organic solvent comprises at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

[0023] In some embodiments, the second organic solvent comprises at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

[0024] In some embodiments, the preparation method of the trianhydride compound comprises the following steps: mixing maleic anhydride and thiocyanic acid trimer to form a uniform solution, adding the thiocyanic acid trimer solution drop by drop, and fully stirring to obtain the trianhydride compound.

[0025] The third embodiment of the present application provides a lithium battery comprising the solid electrolyte film in any of the above embodiments, or the solid electrolyte film prepared by the preparation method in any of the above embodiments.

[0026] The present application provides a solid electrolyte film comprising a polymer electrolyte, wherein the structure of the polymer electrolyte is a hyperbranched polymer, and the molecular chain of the hyperbranched polymer contains polyethylene oxide segments, and the ether oxygen atoms in the non-crystalline phase region can form coordination with lithium ions, which is conducive to the migration of lithium ions and improves the ionic conductivity of the solid electrolyte film; in addition, the hyperbranched polymer introduces nitrogen and sulfur element cyclic structures, which can effectively improve the mechanical strength of the solid electrolyte film, and also further improve the ionic conductivity of the solid electrolyte film and reduce the interface impedance, thereby improving the comprehensive performance of the battery in safety performance and electrical performance. BRIEF DESCRIPTION OF DRAWINGS

[0027] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1 These are graphs showing the performance test results of the solid electrolyte membranes prepared in Examples 1-5 and Comparative Example 1 of this application. Detailed Implementation

[0029] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0030] In the description of this application, it should be noted that "multiple" means two or more, unless otherwise explicitly specified. Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, features defined with "first" or "second" may explicitly or implicitly include one or more features.

[0031] The compounds of this application can be synthesized via synthetic routes including methods similar to those known in the field of chemistry, particularly with reference to the description contained herein. Starting materials are generally available from commercial sources or can be readily prepared using methods known to those skilled in the art. For illustrative purposes, the reaction schemes described below illustrate possible routes for synthesizing the compounds of this application and key intermediates. For a more detailed description of each reaction step, see the Examples section below. Those skilled in the art will recognize that other suitable starting materials, reagents, and synthetic routes can be used to synthesize the compounds of this application and their various derivatives.

[0032] The following disclosure provides many different embodiments or examples for implementing different structures of this application. To simplify the disclosure of this application, the configuration and arrangement of specific examples are described below. Of course, these are merely examples and are not intended to limit this application.

[0033] The first embodiment of this application provides a solid electrolyte membrane, including a polymer electrolyte, the structural formula of which is shown in Formula I:

[0034] Formula I; In the formula, n = 1~100.

[0035] It is understandable that the polymer structure shown in Formula I is a hyperbranched polymer, whose molecular chain contains polyethylene oxide segments. The ether oxygen atoms in the amorphous phase region can coordinate with lithium ions, which is beneficial for lithium ion migration and improves the ionic conductivity of the solid electrolyte membrane. Furthermore, the introduction of nitrogen and sulfur ring structures into the hyperbranched polymer can effectively improve the mechanical strength of the solid electrolyte membrane, while also further improving the ionic conductivity and reducing interfacial impedance, thereby enhancing the overall safety and electrical performance of the battery. The value of n can be any value from 1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, or any value within a range of any two values. When the value of n meets the above range, the branches of the hyperbranched polymer have a relatively ideal length, thus providing sufficient space for lithium ion migration, while ensuring that the solid electrolyte membrane as a whole has good mechanical strength within this branch length range.

[0036] In some embodiments, inorganic electrolytes and lithium salts are also included.

[0037] It is understood that the inorganic electrolyte in this application is an inorganic solid electrolyte. Inorganic solid electrolytes have the characteristics of high conductivity and wide electrochemical window. Using inorganic solid electrolytes as electrolyte membranes can effectively improve the ionic conductivity and ion mobility of solid electrolyte membranes. By mixing polymer electrolytes with inorganic electrolytes to form organic-inorganic composite solid electrolyte membranes, it is possible to combine the advantages of inorganic solid electrolytes and polymer solid electrolytes, that is, to have both good mechanical strength and conductivity.

[0038] Specifically, the mass ratio of polymer electrolyte, inorganic electrolyte and lithium salt is (60~90):(5~20):(5~20).

[0039] Understandably, the mass ratio of polymer electrolyte, inorganic electrolyte, and lithium salt can be any value or a range between any two of the following: 90:5:5, 85:7:8, 80:10:10, 78:12:10, 75:15:10, 72:16:12, 70:18:12, 68:20:12, 65:20:15, 60:20:20. While inorganic electrolytes can improve the ionic conductivity of the composite solid electrolyte membrane, they are also more brittle. Excessive inorganic electrolyte content can lead to a decrease in the mechanical strength of the composite solid electrolyte membrane and may also result in insufficient contact between the membrane and the electrode, causing interfacial impedance and affecting the battery's electrical performance. When the mass ratio of polymer electrolyte, inorganic electrolyte, and lithium salt meets the above-mentioned range, the composite solid electrolyte membrane achieves a balance between mechanical strength and conductivity, resulting in excellent overall performance.

[0040] In some embodiments, the inorganic electrolyte is a solid particle with a particle size of 100~500 nm.

[0041] Understandably, when the inorganic electrolyte is in solid particulate form, it can be uniformly dispersed within the branched structure of the hyperbranched polymer electrolyte, thereby further enhancing the mechanical strength of the composite electrolyte membrane. The particle size of the solid particles can be any value or a range between 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, and 500nm. The particle size of the inorganic electrolyte not only affects the uniformity of dispersion of the inorganic electrolyte in the polymer electrolyte but also has a certain influence on its ionic conductivity. When the particle size of the inorganic electrolyte meets the above-mentioned range, it can ensure that the inorganic electrolyte is well dispersed in the polymer electrolyte, and the solid electrolyte membrane has good mechanical strength as well as good ionic conductivity.

[0042] In some embodiments, the inorganic electrolyte includes Li 3.3 La 0.56 TiO3, Li7La3Zr2O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 Li3P3S 11 Li2P2S6 and Li 10 GeP2S 12 At least one of them.

[0043] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, and lithium perchlorate.

[0044] The second embodiment of this application provides a method for preparing a composite solid electrolyte membrane, used to prepare the composite solid electrolyte membrane in any of the above embodiments, comprising the following steps: The triacid anhydride compound and polyethylene oxide diamine were mixed and stirred for the first time. Acetic anhydride and pyridine were added and stirred for the second time to obtain the polymer electrolyte. The inorganic electrolyte is added to the first organic solvent and then fully dispersed by ball milling to obtain an inorganic electrolyte dispersion. The polymer electrolyte was added to the second organic solvent, heated and stirred for the third time, cooled to room temperature, and then an inorganic electrolyte dispersion and lithium salt were added. The mixture was stirred for the fourth time and dried to obtain a composite solid electrolyte membrane. The structural formula of the triacid anhydride compound is shown in Formula II:

[0045] Formula II.

[0046] It is understandable that the degree of polymerization of polyethylene oxide diamine is 100-5000. By subjecting triacid anhydride compounds to an amidation reaction with polyethylene oxide diamine, using anhydride as an acylating agent and pyridine as a catalyst to promote the amidation reaction, dendritic hyperbranched polymers as shown in Formula I can be formed.

[0047] Furthermore, by fully ball milling and dispersing the inorganic electrolyte, it can exist in the form of ideal solid particles, which helps the inorganic electrolyte to be dispersed in the polymer electrolyte, so that the composite solid electrolyte membrane has good mechanical strength and ionic conductivity.

[0048] In some embodiments, the mass ratio of the triacid anhydride compound to polyethylene oxide diamine is 1:4 to 10.

[0049] It is understandable that the mass ratio of the triacid anhydride compound to the polyethylene oxide diamine can be any value from 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or any value within a range of any two values. When the mass ratio of the triacid anhydride compound to the polyethylene oxide diamine meets the above range, it ensures that the two react fully, forming a hyperbranched structure with moderate branching and regular structure, and a balanced proportion of terminal active groups, which is beneficial for subsequent end-capping and regulation of polymer electrolyte performance.

[0050] In some embodiments, the mass ratio of polymer electrolyte, inorganic electrolyte and lithium salt is (60~90):(5~20):(5~20).

[0051] It is understandable that the mass ratio of the polymer electrolyte, inorganic electrolyte, and lithium salt can be any value or a range between any two of the following: 90:5:5, 85:7:8, 80:10:10, 78:12:10, 75:15:10, 72:16:12, 70:18:12, 68:20:12, 65:20:15, and 60:20:20. When the mass ratio of the polymer electrolyte, inorganic electrolyte, and lithium salt meets the above range, the resulting composite solid electrolyte membrane has a good formulation ratio, achieving a balance between mechanical strength and conductivity, thus exhibiting excellent overall performance.

[0052] In some embodiments, the temperature of the first stirring is 15~30℃, and the time is 20~30h.

[0053] Understandably, the temperature for the first stirring can be any value from 15℃, 20℃, 25℃, and 30℃, or any value within a range of two such values. The stirring time can be any value from 20h, 22h, 24h, 26h, 28h, and 30h, or any value within a range of two such values. By controlling the temperature and time of the first stirring to meet these ranges, it is possible to ensure the complete reaction of the triacid anhydride compound and the polyethylene oxide diamine, while avoiding the formation of side reactants.

[0054] In some embodiments, the temperature of the second stirring is 15~30℃, and the time is 10~20h.

[0055] It is understandable that the temperature for the second stirring can be any value or a range between any two of 15℃, 20℃, 25℃, and 30℃, and the stirring time can be any value or a range between any two of 10h, 12h, 14h, 16h, 18h, and 20h.

[0056] In some embodiments, the temperature of the third stirring is 45~85℃, and the time is 2~5h.

[0057] Understandably, the temperature for the third stirring can be any value or a range between any two of the following: 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, and 85℃. The stirring time can be any value or a range between any two of the following: 2h, 3h, 4h, and 5h. By controlling the temperature and time of the third stirring to meet the above-mentioned ranges, the polymer electrolyte is fully dissolved in the second organic solvent.

[0058] In some embodiments, the fourth stirring is performed at room temperature for 1 to 3 hours.

[0059] It is understandable that the time for the fourth stirring can be any value from 1h, 2h, and 3h, or a value within a range of any two values. By controlling the temperature and time of the fourth stirring to meet the above range, the polymer electrolyte, inorganic electrolyte, and lithium salt can be thoroughly and uniformly mixed.

[0060] In some embodiments, the inorganic electrolyte includes Li 3.3 La 0.56 TiO3, Li7La3Zr2O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 Li3P3S 11 Li2P2S6 and Li 10 GeP2S 12 At least one of them.

[0061] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, and lithium perchlorate.

[0062] In some embodiments, the first organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

[0063] In some embodiments, the second organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

[0064] In some embodiments, the preparation method of the trianic anhydride compound includes the following steps: Maleic anhydride and trithiocyanate are mixed to form a homogeneous solution. The trithiocyanate solution is added dropwise and stirred thoroughly to obtain the tri-anhydride compound.

[0065] Specifically, the solid electrolyte membrane provided in this application can be prepared by the following steps: S1. Maleic anhydride and trithiocyanate were added to N,N-dimethylacetamide and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 3-10 hours to prepare the triic anhydride compound. S2. Polyoxyethylene diamine was added to the triacid anhydride compound and stirred at 15-30°C for 20-30 h. Acetic anhydride and pyridine were added and stirring was continued for 10-20 h. Finally, the mixture was washed several times with ethanol and filtered to prepare the hyperbranched polymer electrolyte. S3. Add the inorganic electrolyte to a ball mill containing N,N-dimethylacetamide and disperse it thoroughly by ball milling to obtain an inorganic electrolyte dispersion. S4. Add the hyperbranched polymer electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 45~85℃ for 2~5h, cool to room temperature, add inorganic electrolyte dispersion, and add lithium salt at the same time, continue stirring for 1~3h to obtain a mixed solution, coat the prepared mixed solution on a polytetrafluoroethylene mold, dry, and obtain a solid electrolyte membrane.

[0066] The third embodiment of this application provides a lithium battery, including the solid electrolyte membrane in any of the above embodiments, or including the solid electrolyte membrane prepared by the preparation method in any of the above embodiments.

[0067] Specifically, a lithium battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane is disposed between the positive electrode and the negative electrode.

[0068] The composite solid electrolyte membrane and its preparation method, as well as the lithium battery provided in this application, are described below with reference to specific embodiments: Example 1: S1. 29.78 g of maleic anhydride and 17.73 g of trithiocyanate were added to 100 mL of N,N-dimethylacetamide solution and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 5 h to prepare the triacid anhydride compound. S2. Add 200g of polyethylene oxide diamine to the triacid anhydride compound, stir at 15°C for 30h, add 0.5g of acetic anhydride and 0.5g of pyridine, continue stirring for 15h, finally wash three times with ethanol, filter, and prepare hyperbranched polymer solid electrolyte. S3, Add 5gLi 3.3 La 0.56T iO3 was added to a ball mill containing N,N-dimethylacetamide and thoroughly dispersed by ball milling to obtain Li. 3.3 La 0.56 TiO3 dispersion; S4. Add 90g of hyperbranched polymer solid electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 75℃ for 3h, cool to room temperature, and add Li. 3.3 La 0.56TiO3 dispersion was prepared by adding 5g of lithium salt and stirring for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a hyperbranched polymer solid electrolyte membrane.

[0069] Example 2: S1. 29.78 g of maleic anhydride and 17.73 g of trithiocyanate were added to 100 mL of N,N-dimethylacetamide solution and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 5 h to prepare the triacid anhydride compound. S2. Add 300g of polyethylene oxide diamine to the triacid anhydride compound and add 30mL of N,N-dimethylacetamide solvent. Stir at 15℃ for 30h, add 0.5g of acetic anhydride and 0.5g of pyridine, continue stirring for 15h, and finally wash three times with ethanol and filter to prepare hyperbranched polymer solid electrolyte. S3, Add 5g Li 3.3 La 0.56 TiO3 was added to a ball mill containing N,N-dimethylacetamide and thoroughly dispersed by ball milling to obtain Li. 3.3 La 0.56 TiO3 dispersion; S4. Add 90g of hyperbranched polymer solid electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 75℃ for 3h, cool to room temperature, and add Li. 3.3 La 0.56 TiO3 dispersion was prepared by adding 5g of lithium salt and stirring for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a hyperbranched polymer solid electrolyte membrane.

[0070] Example 3: S1. 29.78 g of maleic anhydride and 17.73 g of trithiocyanate were added to 100 mL of N,N-dimethylacetamide solution and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 5 h to prepare the triacid anhydride compound. S2. Add 300g of polyethylene oxide diamine to the triacid anhydride compound and add 30mL of N,N-dimethylacetamide solvent. Stir at 15℃ for 30h, add 0.5g of acetic anhydride and 0.5g of pyridine, continue stirring for 15h, and finally wash three times with ethanol and filter to prepare hyperbranched polymer solid electrolyte. S3, Add 10g Li 3.3 La 0.56 TiO3 was added to a ball mill containing N,N-dimethylacetamide and thoroughly dispersed by ball milling to obtain Li. 3.3 La 0.56 TiO3 dispersion; S4. Add 85g of hyperbranched polymer solid electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 75℃ for 3 hours, cool to room temperature, and add Li. 3.3 La 0.56 TiO3 dispersion was prepared by adding 5g of lithium salt and stirring for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a hyperbranched polymer solid electrolyte membrane.

[0071] Example 4: S1. 29.78 g of maleic anhydride and 17.73 g of trithiocyanate were added to 100 mL of N,N-dimethylacetamide solution and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 5 h to prepare the triacid anhydride compound. S2. Add 300g of polyethylene oxide diamine to the triacid anhydride compound and add 30mL of N,N-dimethylacetamide solvent. Stir at 15℃ for 30h, add 0.5g of acetic anhydride and 0.5g of pyridine, continue stirring for 15h, and finally wash three times with ethanol and filter to prepare hyperbranched polymer solid electrolyte. S3, Add 20g Li 3.3 La 0.56 TiO3 was added to a ball mill containing N,N-dimethylacetamide and thoroughly dispersed by ball milling to obtain Li. 3.3 La 0.56 TiO3 dispersion; S4. Add 75g of hyperbranched polymer solid electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 75℃ for 3h, cool to room temperature, and add Li. 3.3 La 0.56 TiO3 dispersion was prepared by adding 5g of lithium salt and stirring for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a hyperbranched polymer solid electrolyte membrane.

[0072] Example 5: S1. 29.78 g of maleic anhydride and 17.73 g of trithiocyanate were added to 100 mL of N,N-dimethylacetamide solution and dispersed evenly. Then, the trithiocyanate solution was added dropwise to the maleic anhydride solution and stirred at room temperature for 5 h to prepare the triacid anhydride compound. S2. Add 300g of polyethylene oxide diamine to the triacid anhydride compound and add 30mL of N,N-dimethylacetamide solvent. Stir at 15℃ for 30h, add 0.5g of acetic anhydride and 0.5g of pyridine, continue stirring for 15h, and finally wash three times with ethanol and filter to prepare hyperbranched polymer solid electrolyte. S3, Add 10g Li3.3 La 0.56 TiO3 was added to a ball mill containing N,N-dimethylacetamide and thoroughly dispersed by ball milling to obtain Li. 3.3 La 0.56 TiO3 dispersion; S4. Add 80g of hyperbranched polymer solid electrolyte to a stirred tank containing N,N-dimethylacetamide, stir at 75℃ for 3h, cool to room temperature, and add Li. 3.3 La 0.56 TiO3 dispersion was prepared by adding 10g of lithium salt and stirring for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a hyperbranched polymer solid electrolyte membrane.

[0073] Comparative Example 1: Take 85g of polyethylene oxide and 10g of Li 3.3 La 0.56 TiO3 and 5g of lithium bis(trifluoromethanesulfonyl)imide were dispersed in N,N-dimethylacetamide and stirred for 2 hours. The prepared solution was then coated onto a polytetrafluoroethylene mold and dried to obtain a polyoxyethylene composite solid electrolyte membrane.

[0074] The solid electrolyte membranes prepared in the above embodiments and comparative examples were subjected to performance testing, including the following steps: Mechanical strength test method: Refer to GB / T36363-2018 standard, and test the mechanical strength of the composite solid electrolyte membrane at a rate of 10 mm / min under universal tensile test.

[0075] Ionic conductivity test: The ionic conductivity of the electrolyte is calculated by assembling a symmetrical cell with a steel sheet as the blocking electrode on an electrochemical workstation at a frequency range of 0.1 Hz to 106 Hz, according to the following working time: σ = L / (R×S), where σ is the ionic conductivity of the composite solid electrolyte membrane, L is the thickness of the composite solid electrolyte membrane, S is the area of ​​the composite solid electrolyte membrane, and R is the bulk resistance of the composite solid electrolyte membrane.

[0076] Test results are as follows Figure 1 As shown.

[0077] according to Figure 1It can be seen that the solid electrolyte membrane obtained by using the technical solution provided in this application exhibits relatively ideal performance in both mechanical strength and ionic conductivity. According to Comparative Example 1, when linear polyethylene oxide is used as the polymer electrolyte, the resulting solid electrolyte membrane is not ideal in terms of both mechanical strength and ionic conductivity. A comparison of Examples 1 and 2 shows that increasing the amount of polyethylene oxide diamine during the preparation of the polymer electrolyte can, to a certain extent, promote the full reaction of the reactants and increase the number of ether oxygen atoms in the amorphous phase region, which is beneficial for lithium ion migration, thereby improving the mechanical strength and ionic conductivity of the polymer electrolyte. A comparison of Examples 1 and 3 shows that appropriately increasing the proportion of inorganic electrolyte can effectively improve the overall performance of the composite solid electrolyte membrane; however, according to Example 4, a smaller amount of polymer electrolyte will cause a decline in mechanical properties.

[0078] The composite solid electrolyte membrane and its preparation method, as well as the lithium battery, provided in the embodiments of this application have been described in detail above. Specific examples have been used in this application to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the technical solutions and core ideas of this application. Those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A solid electrolyte membrane, characterized in that, It includes a polymer electrolyte, the structural formula of which is shown in Formula I: Formula I; In the formula, n = 1~100.

2. The solid electrolyte membrane according to claim 1, characterized in that, It also includes inorganic electrolytes and lithium salts; The mass ratio of the polymer electrolyte, the inorganic electrolyte and the lithium salt is (60~90):(5~20):(5~20).

3. The solid electrolyte membrane according to claim 2, characterized in that, The inorganic electrolyte is a solid particle with a particle size of 100~500nm.

4. The solid electrolyte membrane according to claim 2, characterized in that, The inorganic electrolyte includes Li 3.3 La 0.56 TiO3, Li7La3Zr2O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 Li3P3S 11 Li2P2S6 and Li 10 GeP2S 12 At least one of them; and / or, The lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, and lithium perchlorate.

5. A method for preparing a solid electrolyte membrane as described in any one of claims 1 to 4, characterized in that, Includes the following steps: The triacid anhydride compound and polyethylene oxide diamine were mixed and stirred for the first time. Acetic anhydride and pyridine were added and stirred for the second time to obtain the polymer electrolyte. The inorganic electrolyte is added to the first organic solvent and then fully dispersed by ball milling to obtain an inorganic electrolyte dispersion. The polymer electrolyte is added to a second organic solvent, heated and stirred for a third time, cooled to room temperature, the inorganic electrolyte dispersion and lithium salt are added, stirred for a fourth time, and dried to obtain the solid electrolyte membrane. The structural formula of the trianic anhydride compound is shown in Formula II: Formula II.

6. The method for preparing a solid electrolyte membrane according to claim 5, characterized in that, The mass ratio of the triacid anhydride compound to polyethylene oxide diamine is 1:4~10; and / or, The mass ratio of the polymer electrolyte, the inorganic electrolyte and the lithium salt is (60~90):(5~20):(5~20).

7. The method for preparing a solid electrolyte membrane according to claim 5, characterized in that, The temperature of the first stirring is 15~30℃, and the time is 20~30h; and / or, The second stirring is performed at a temperature of 15-30°C for 10-20 hours; and / or, The third stirring is performed at a temperature of 45-85°C for 2-5 hours; and / or, The fourth stirring was performed at room temperature for 1-3 hours.

8. The method for preparing a solid electrolyte membrane according to claim 5, characterized in that, The inorganic electrolyte includes Li 3.3 La 0.56 TiO3, Li7La3Zr2O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li 1.4 ZnGe4O 16 Li3P3S 11 Li2P2S6 and Li 10 GeP2S 12 At least one of them; and / or, The lithium salt comprises at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate, lithium difluorooxalate borate, and lithium perchlorate; and / or, The first organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide; and / or, The second organic solvent includes at least one of N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylformamide.

9. The method for preparing a solid electrolyte membrane according to claim 5, characterized in that, The preparation method of the trianic anhydride compound includes the following steps: Maleic anhydride and trithiocyanate are mixed to form a homogeneous solution. The trithiocyanate solution is added dropwise and stirred thoroughly to obtain the tri-anhydride compound.

10. A lithium battery, characterized in that, Includes a solid electrolyte membrane as described in any one of claims 1 to 4, or includes a solid electrolyte membrane prepared by the preparation method as described in any one of claims 5 to 9.

Citation Information

Patent Citations

  • Shape memory polyimide prepared by virtue of chemical imidization and preparation method thereof

    CN103980490A

  • Naphthalene structure-containing high heat-resistant hyperbranched polyimide as well as preparation method and application thereof

    CN108976420A

  • Naphthalene-structure-containing hyperbranched polyimide and preparing method and application thereof

    CN109134860A

  • Polyimide film as well as preparation method and application thereof

    CN114685786A

Cited By

  • Preparation and application of diaphragm in-situ initiated hyperbranched polymer electrolyte

    CN121507130A